Remote Digital Microscopy Improves Hematology Laboratory Workflow by Reducing Peripheral Blood Smear Analysis Turnaround Time - Katz, Ben-Zion; Benisty, Dan; Sayegh, Yael; Lamm, Inna; Avivi, Irit (Applied Clinical Informatics, 2022)
Background The demand for morphological diagnosis by peripheral blood smear (PBS) analysis with clearly defined turnaround times (TAT), coupled with a shortage of morphologists and increasing cost containment, is driving digitalization to the forefront of laboratory workflow. Labor-intensive manual PBS review affects weekend workflow with limited staff availability. The impact of remote analysis of PBS on the performance of hematology laboratories has not yet been assessed.Objectives Following implementation of fully remote digital microscopy within our laboratory, we measured its impact on morphology workflow efficiency, TAT, and hours saved per month.Methods A retrospective study of the effects of remote PBS analysis on the morphology workflow in a tertiary medical center using the Scopio Labs X100 Full-Field PBS system was conducted. 10,704 PBS samples were analyzed pre-and post -implementation, over a 5-month period. Overall PBS workload, and average TAT of PBS samples over weekends and the first two weekdays were collected and evaluated.Results Remote weekend viewing resulted in a 15.8% reduction in the overall morphology TAT of the laboratory (p <0.03) over a 5-month period, despite similar overall workload. PBS analysis TAT on Fridays was reduced by 41.4% (p <0. 006), and by 59.1% on the first weekday (p <0.02). The additional hours incurred over the weekend were offset against a reduced need for double weekday shifts resulting in approximately 12.76 work hours saved per month. Internet links to clinically relevant cases are provided.Conclusion The Scopio Labs Full-Field X100 PBS system with remote analysis capacity significantly reduced PBS TAT and improved the morphology workflow of the hematology laboratory. PBSs with significant clinical findings are now available for remote viewing by on-call clinicians located outside the medical center perimeter. Remote PBS viewing, coupled with the overall monthly cost savings, merit consideration for the implementation of full digitalization for remote PBS review.
Keywords: digital; efficiency; hematology; morphology; peripheral blood smear; remote; workflow